Promotion of Beauveria bassiana Mushroom on Different Growing Media and Its Pathogenicity on Insects - Lukmanul Hakim; Yenny Wuryandari (Nusantara Science and Technology Proceedings, 2022)
One type of entomopathogenic fungus that is known to be effective in controlling important plant pests is the Beauveria bassiana fungus. The fungus B. bassiana, has a high reproductive capacity, is easy to produce and under unfavorable conditions can form spores that can last a long time in nature. The purpose of this study was to determine the density and viability of B. bassiana spores on corn and rice media and to investigate the process of B. bassiana fungal infection in the test insects. The method used is; Fungal propagation test on Rice and Corn Media, Microscopic Observation of Fungus from Corn and Rice Media, Calculation of Fungus Spore Density, Calculation of Fungus Viability and Pathogenicity Test. The research results obtained are as follows; Results The propagation of B. bassiana mushroom grew on the seventh day, the fungus growth was faster in rice media than in corn media. The spore density of the fungus B. bassiana clove bondowoso in corn media was 3.75x108 spores/ml, rice media was 4.58x108 spores/ml, B. bassiana banyuwangi coffee medium was 3.5x108 spores/ml, rice media was 3.75x108 spores/ml. The viability of the fungus B. bassiana, clove bondowoso and banyuwangi coffee on rice and corn media was obtained on average above 60%. The results of the pathogenicity test of B. bassiana on insects began to appear on the tenth day after the baiting process.